2009
DOI: 10.1128/aac.00689-09
|View full text |Cite
|
Sign up to set email alerts
|

ATP Synthase Inhibition of Mycobacterium avium Is Not Bactericidal

Abstract: The efficacy of ATP synthase inhibitor TMC207 was assessed in early and late Mycobacterium avium infections in mice. In contrast to what was earlier observed for M. tuberculosis, a bacteriostatic effect was obtained. In vitro, the minimal bactericidal concentration (MBC)/MIC ratio was very high. The MBC was more relevant for assessment of pharmacokinetic/pharmacodynamic relationships than the MIC.Mycobacterium avium is a pathogen that causes disseminated disease in immunocompromised individuals and pulmonary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 16 publications
(19 reference statements)
0
31
1
1
Order By: Relevance
“…A diff erence in treatment response for MAC and MTB in a murine model was assumed to be attributable, in part, to the diff erence in killing activity of the two species. 11 Another factor is that virtually all patients had been on the complimentary drugs for prolonged periods of time with minimal or no response. A fi nal factor is the possible development of bedaquiline resistance before any clinical or microbiologic benefi t could be measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diff erence in treatment response for MAC and MTB in a murine model was assumed to be attributable, in part, to the diff erence in killing activity of the two species. 11 Another factor is that virtually all patients had been on the complimentary drugs for prolonged periods of time with minimal or no response. A fi nal factor is the possible development of bedaquiline resistance before any clinical or microbiologic benefi t could be measured.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Although bedaquiline has impressive in vitro activity for NTM, the clinical activity of the drug among individuals with NTM lung disease has not been studied. We describe the treatment with bedaquiline-containing regimens of individuals with refractory Mab or MAC lung disease who remained acid-fast bacilli (AFB) culture positive despite aggressive guidelines-directed therapy.…”
Section: [ 1 4 8 # 2 C H E S T a U G U S T 2 0 1 5 ]mentioning
confidence: 99%
“…When used alone, the drug is not bactericidal against MAC in vitro or in vivo (minimum bactericidal concentration [MBC], Ͼ128 g/ml). However, when BDQ is given in combination with amikacin or amikacin plus clarithromycin, bactericidal activity is observed after 3 to 4 months of treatment (14). In 2015, the first study describing the off-label use of BDQ for the treatment of patients with refractory MDR NTM was reported by Philley et al (15).…”
mentioning
confidence: 99%
“…In an early intraperitoneal infection murine model (treatment started on the day after infection), Lounis et al (15) showed that 1 month of five times weekly monotherapy with clarithromycin and bedaquiline decreased the CFU counts of MAC by 1.99 and 2.56 log10 compared to those of untreated controls (P ϭ 0.005 and P ϭ 0.002, respectively). In a late intraperitoneal infection murine model (mice untreated for 1 month and then treated for 4 months), bactericidal activity was achieved following 3 months of triple treatment with clarithromycin plus amikacin plus bedaquiline (P ϭ 0.001).…”
mentioning
confidence: 99%